Medical terminology in new age Serbia: over 150 years of existence - Ankica (General Practice, 2023)
The marking of the anniversary in 2022 was of great importance for medical terminology in Serbia. After the first, short-lived institutionalization in the Društvo srpske slovesnosti in 1842 this topic became part of the work assignments and activities of an institution, for the second time. This time it was for the Serbian Medical Society (SMS) right after its foundation in 1872. Every randomness in this area was disabled by very clear and precise attitudes established by the first Constitution of SMS. In this area of our medical science, besides founders and first members of SMS, the special place belongs to physicians Jovan Stejic, Milan Jovanovic- Batut, Radivoje Pavlovic, Aleksandar Kostic, Aleksandar Belic, and others. Nowadays, medical terminology is no longer a part of the Constitution of the SMS. It is not yet clear how this happened, nor who, if any, other institution, has taken this huge obligation and responsibility for the development, improvement, and maintenance of medical terminology in the Serbian language. Its creation needs the cooperation of professionals from different walks of education, first of all, physicians and experts in the Serbian language, because it is a matter of foundation, almost identity values. It is necessary to make proper terms and interpret them precisely. The absence of this inevitably leads, not only to a standstill, but collapsing of the already achieved that would instead of enriching only impoverish the Serbian language.